The effectiveness of normative messages to decrease meat consumption: The superiority of dynamic normative messages framed as a loss - De Groot, Judith Irene Maria (Frontiers in Sustainability, 2022)
Consumer behaviors related to food consumption, such as meat consumption, is acknowledged to be a main contributor to environmental problems. Recent research supports the efficacy of normative messages to change these behaviors for the good. Normative messages make salient the social norm in a behavioral context. Research shows that normative messages are effective to encourage "desired" pro-environmental behavior if this behavior is carried out by a numerical majority. However, pro-environmental consumer behaviors are often carried out by a minority only. Making salient these minority behaviors in normative messages often backfires because the normative message makes salient that it is normal to perform the "undesirable" environmentally-harmful behavior. To overcome this shortfall, research has experimented with highlighting that the desired behavior, although still a minority behavior, has increased in prevalence (i.e., a dynamic rather than static normative message). However, when such dynamic normative messages are most effective is less clear. Specifically, according to goal-framing theory, it can be assumed that a dynamic normative message highlighting that an increasing minority of people start carrying out the desirable behavior represents a gain frame, while emphasizing that the majority behavior is decreasing indicates a loss frame. So far, research on dynamic normative messages only applied gain frames in their messages. This is surprising, as construal level theory suggests that dynamic normative messages will be more effective when framed as a loss. The present study therefore tested whether a dynamic normative message is more effective than a static normative message or no message at all, depending on whether it is framed as a loss or a gain. In a one-way between-subject experimental design, including five experimental conditions (i.e., static descriptive normative message (1) gain-framed or (2) loss framed; dynamic descriptive normative message (3) gain-framed or (4) loss-framed; (5) control condition; N=270), we found that only dynamic normative messages that were framed as a loss, were more effective in encouraging a consumer’s intention to reduce meat consumption. Therefore, dynamic normative messages are effective to encourage minority pro-environmental consumer behaviors, but especially when they are framed as a loss rather than a gain.